Legal Certainty Regarding Mandatory Legal Entity Adjustment for Regional Enterprises - Amelia Sri Kusuma Dewi; Fairial Fatimah (Universitas Islam Sultan Agung, 2026)
This study aims to analyze the realization of legal certainty in the regulation concerning the obligation to adjust the legal entity form of Regionally Owned Enterprises (Badan Usaha Milik Daerah/BUMD), particularly those owned by the Provincial Government of East Java, as mandated under Article 402 paragraph (2) of Law Number 23 of 2014 concerning Regional Government. The research problem focuses on the fact that a number of BUMDs have not yet adjusted their legal entity forms despite the expiration of the statutory transitional period, thereby raising issues concerning legal standing, adjustment mechanisms, and the legal status of such enterprises. The research employs a normative juridical (dogmatic) method using both statutory and conceptual approaches. The study was conducted through library research on primary, secondary, and tertiary legal materials, which were analyzed descriptively and qualitatively using the theories of legal certainty advanced by Gustav Radbruch, Hans Kelsen, and Utrecht. The novelty of this research lies in its comprehensive analysis of the disharmony and normative vacuum within the regulation of the obligation to adjust the legal entity forms of BUMDs at the levels of legislation, government regulations, and regional regulations of East Java Province, particularly regarding adjustment mechanisms, legal sanctions, and the juridical status of BUMDs that have failed to comply with the adjustment requirement. The study concludes that the regulatory framework concerning the obligation to adjust the legal entity forms of BUMDs under the Regional Government Law, Government Regulation Number 54 of 2017, and the Regional Regulations of East Java Province on BUMDs and their amendments has not fully realized legal certainty due to the persistence of legal vacuums, normative conflicts, and unclear juridical consequences for BUMDs that have not undertaken the required legal entity adjustment in accordance with statutory mandates.